PULPS TO THE SODA-AQ OF PINE FOR PRODUCTION OF PAPER WAVE, LINER AND NEWSPAPER - Felissia, Fernando E.; Cristina Area, María; Clermont, Javier; Moral, Manuel (Centro Azúcar Journal, 2006)
The objective of this work was to verify the potentiality from the pulps to the soda-antraquinona of pine for the production of papers wave, liner and newspaper (blended with trash pulp), using adapted technological outlines of one manufactures of trash pulps. The work was carried out with pine chips coming from the north area of Missions, according to a prosecution indicated by Tucumán paper mill. In the case of liner and wave, the reached yield was of 67 % and the results indicated that the used process (soda-AQ of pine, with impregnation of 25 % of the chips) it is adapted for the obtaining of pulp brown semichemical. The obtained pulp presented a quality more than enough to be used in the production of papers liner, being in the inferior limit of quality for the production of papers wave (130 g/m2, RCT 1,56 kN/m, CMT 172 N). with regard to the periodic paper, the pulp with yield of 61 % was refined blended with trash pulp in different proportions and it was whitened with NaClO with an objective target of 70 %ISO. The best mixture was that of 90% of trash pulp and 10 % of pulp pine semichemical.